Laboratory Simulation of Electricity Harvesting from an Underwater Kite. Issue 37 (2022) - Tiburcio, Miguel Alvarez; Bhattacharjee, Debapriya; Kadkhodaeielyaderani, Behzad; Fathy, Hosam K.
Abstract: This paper addresses the problem of experimentally characterizing the energy conversion losses associated with electricity harvesting from tethered marine hydrokinetic kites. The authors present a laboratory setup intended for this characterization. The setup utilizes two geared brushless DC electric machines. The first electric machine is intended for energy harvesting from a scaled kite system in a lake environment. The second electric machine is used in the laboratory for emulating the mechanical loads associated with energy harvesting, thereby allowing the setup to operate as a hardware-in-the-loop testing system. Experiments conducted using this system, for a kite flight trajectory optimized for mechanical power harvesting, reveal a significant discrepancy between the mechanical power seen at the tether release drum versus the electrical power ultimately generated. Simple linear regression shows that much of this discrepancy can be attributed to mechanical friction within the setup (including the electric machine's gearing), as opposed to electrical impedance. This creates a strong motivation for additional research on trajectory optimization for electrical power generation.